2021
DOI: 10.7759/cureus.19932
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy of Plasma Exchange and Rituximab to Treat Cicatricial Pemphigoid and Bullous Pemphigoid

Abstract: The pemphigoid group of subepidermal autoimmune blistering diseases can affect both cutaneous and mucosal tissues. Therapy of this group of diseases, including cicatricial pemphigoid (CP) and bullous pemphigoid (BP), consists of systemic steroids and immunomodulatory agents. Recalcitrant cases have typically been treated with plasmapheresis or rituximab individually. This report describes two patients with severe, rapidly progressive CP and BP refractory to high-dosage systemic steroids and immunomodulatory ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…10 The decision to discontinue TPE in human patients is based on monitoring the clinical improvement and/or anti-desmoglein titers; it is often carried out over several weeks to months in human pemphigus patients. 9,11,12 In our case, TPE was discontinued after 1 week based on improved clinical response and as a consequence of financial constraints limiting additional TPE sessions. The extended application of TPE alongside adjunctive interventions such as human immunoglobulin therapy may have resulted in a better outcome in this patient.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…10 The decision to discontinue TPE in human patients is based on monitoring the clinical improvement and/or anti-desmoglein titers; it is often carried out over several weeks to months in human pemphigus patients. 9,11,12 In our case, TPE was discontinued after 1 week based on improved clinical response and as a consequence of financial constraints limiting additional TPE sessions. The extended application of TPE alongside adjunctive interventions such as human immunoglobulin therapy may have resulted in a better outcome in this patient.…”
Section: Discussionmentioning
confidence: 97%
“…In human medicine, the application of TPE for the treatment of pemphigus is considered for cases where standard therapies have been ineffective. The procedure has yielded significant reductions in circulating autoantibodies, leading to clinical improvement and a reduction in the severity of the disease 9–12 . There is a scarcity of literature published on the use of TPE for the treatment of pemphigus in veterinary medicine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the experience of Chang et al, Kitabata et al, and Nasu et al who used systemic steroids and plasma exchange concomitantly, in our case, we observed that therapeutic plasma exchange could obviate the use of systemic immunosuppression. [10][11][12][15][16][17] In our patient, the extremely high levels of autoantibodies recognized after dilution may have played a role in this patient's relapse, highlighting the efficacy of therapeutic plasmapheresis in quickly reducing the high titer of pathogenic autoantibodies and inducing remission. Moreover, the possible effect of therapeutic plasma exchange on the complement protein system and immunomodulation of the immune system should not be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the patient's underlying clinical status (age, diabetes mellitus, chronic HD) and associated high risk of systemic immunosuppressive side effects, the decision was made to perform therapeutic plasmapheresis, rather than give high-dose systemic steroids. [10][11][12] Contrary to the United States, DFPP is approved in Europe and Japan. In DFPP, the plasma is first separated by a plasma filter, and then the separated plasma is filtered through a second filter (plasma fractionator).…”
Section: Case Reportmentioning
confidence: 99%